2020
DOI: 10.21276/ijcmsr.2020.5.1.18
|View full text |Cite
|
Sign up to set email alerts
|

MR Evaluation in non Traumatic Chronic Wrist Pain

Abstract: How to cite this article:Vivek Chail, Abhijit N, Rajan Balasubramanyam, Roohi Singh, Riyanka Chail. MR evaluation in non traumatic chronic wrist pain. International Journal of Contemporary Medicine Surgery and Radiology. 2020;5(1):A79-A84. study the epidemiology and most common causes of non-traumatic chronic wrist pain in the South Indian population and to study the spectrum of MRI features in those patients. Material and methods: Prospective descriptive study was done on 30 patients of both sex and age rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
Order By: Relevance
“…In this study patients in young age group (25-30) had the highest ratio of wrist joint abnormalities. This result was in agreement with Chail et al [14] and El Shibiny et al [16] who stated that most of the cases fall into the age group .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study patients in young age group (25-30) had the highest ratio of wrist joint abnormalities. This result was in agreement with Chail et al [14] and El Shibiny et al [16] who stated that most of the cases fall into the age group .…”
Section: Discussionsupporting
confidence: 92%
“…Its percentage was 8% in this study. Chail, et al [14] reported in study carried out in 2020 that abnormality represented only 6.7%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation